Multiserial rings - Kirichenko, V. V.; Yaremenko, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We introduce the notion of multiserial (n-serial) rings and study their properties. The second-order minors of such rings are investigated. We also find all possible forms of quivers for Noetherian and hereditaryn-serial rings and describe the structure of semiprime and hereditaryn-serial rings.